2009
DOI: 10.1177/0960327109104498
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects associated with arginine α-ketoglutarate containing supplements

Abstract: The athletic performance supplement industry is a multibillion-dollar business and one popular category claims to increase nitric oxide (NO) production. We report three patients presenting to the emergency department with adverse effects. A 33-year-old man presented with palpitations, dizziness, vomiting, and syncope, after the use of NO2 platinum. His examination and electrocardiogram (ECG) were normal. The dizziness persisted, requiring admission overnight. A 21-year-old man wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Moreover, there were no significant differences between subjects for each of these measures ( Table 1). In addition, three subjects reported side effects such as itchy skin, nausea, tachycardia, and flushed face, which has also been previously reported [24]. Subjects reported that these symptoms distracted them mostly during the 45 minute pre-exercise period (since they were required to sit still), and that they were hardly noticeable during the exercise and did not adversely affect their exercise performances.…”
Section: Subject Characteristics and Reported Side Effectssupporting
confidence: 63%
“…Moreover, there were no significant differences between subjects for each of these measures ( Table 1). In addition, three subjects reported side effects such as itchy skin, nausea, tachycardia, and flushed face, which has also been previously reported [24]. Subjects reported that these symptoms distracted them mostly during the 45 minute pre-exercise period (since they were required to sit still), and that they were hardly noticeable during the exercise and did not adversely affect their exercise performances.…”
Section: Subject Characteristics and Reported Side Effectssupporting
confidence: 63%
“…In this regard, a recent paper reported that individuals had experienced adverse side effects following ingestion of nitric oxide stimulator supplements [39]. However, other investigators (as in the current study) have reported that acute ingestion of AAKG ingestion appears to be safe and well tolerated in healthy subjects [13].…”
Section: Discussionmentioning
confidence: 58%
“…Since 2009 there have been several reported cases of adverse outcomes linked to N.O.-Xplode, including a case series of 12 patients with mild to moderate hepatitis, 6 one case of ischemic colitis, 7 and one case of palpitations and headache. 8 The patient presented here is the first documented case of renal failure in someone taking N.O.-Xplode. Even after a pattern of adverse outcomes, N.O.-Xplode remains available to the public and carries no safety warnings.…”
Section: Discussionmentioning
confidence: 85%
“…The previous cases associating N.O.-Xplode with side effects or organ dysfunction focused on nitric oxide and its precursors, L-arginine and arginine ␣-ketoglutarate, because of their vasodilatory effects and effect on hemodynamics. 7,8 While supplemental nitric oxide may have caused palpitations, headache, and ischemic colitis in previous cases, it probably cannot be blamed for renal failure. Rather, nitric oxide is thought to be renally protective.…”
Section: Supplement Factsmentioning
confidence: 99%